Curcumin in Combined Cancer Therapy - Gall Troselj, Koraljka; Novak Kujundzic, Renata (Current Pharmaceutical Design, 2014)
The mechanisms of beneficial preventive and therapeutic effects achieved by traditional and complementary medicine are currently being deciphered in molecular medicine. Curcumin, a yellow-colored polyphenol derived from the rhizome of turmeric (Curcuma longa), influences a wide variety of cellular processes through the reshaping of many molecular targets. One of them, nuclear factor kappa B (NF-ΚB), represents a strong mediator of inflammation and, in a majority of systems, supports the pro-proliferative features of cancer cells. The application of various anticancer drugs, cytostatics, triggers signals which lead to an increase in cellular NF-ΚB activity. As a consequence, cancer cells often reshape their survival signaling pathways and, over time, become resistant to applied therapy. Curcumin was shown to be a strong inhibitor of NF-ΚB activity and its inhibitory effect on NF-ΚB related pathways often leads to cellular apoptotic response. All these facts, tested and confirmed in many different biological systems, have paved the way for research aimed to elucidate the potential beneficial effects of combining curcumin and various anti-cancer drugs in order to establish more efficient and less toxic cancer treatment modalities. This review addresses certain aspects of NF-ΚB-related inflammatory response, its role in carcinogenesis and therapy benefits that may be gained through silencing NF-ΚB by selectively combining curcumin and various anticancer drugs.
Keywords: inflammation